Mengurangi Bullying melalui Program Pelatihan â€œGuru Peduliâ€ - Saptandari, Edilburga Wulan; Adiyanti, MG (Faculty of Psychology, Universitas Gadjah Mada, 2013)
This study investigated a strategy of reducing bullying in elementary school through â€œGuru Peduliâ€ (â€œTeacher Careâ€) training. It was a training done for teachers. It aimed to increase teachersâ€™ awareness, knowledge and skills to prevent and reduce bullying. The aim of this quasi-experimental research was to test the effectiveness of â€œGuru Peduliâ€ training for reducing elementary school bullying. Two elementary schools were involved as the experimental and control groups. There were six classes were for class observation and six locations for playground observation. The observations were done before and after the training. The data were analyzed with Wilcoxon Signed-Rank and Mann-Whitney test. The data showed that there was a significant difference of bullying between the experimental and control schools. There was also a significant reduction of bullying in experimental school after the training. Keywords: bullying, â€œGuru Peduliâ€ training, teachersâ€™ knowledge